2011
DOI: 10.1590/s0102-37722011000100005
|View full text |Cite
|
Sign up to set email alerts
|

Auto-eficácia, raciocínio verbal e desempenho escolar em estudantes

Abstract: RESUMO -Este estudo analisa a relação entre auto-eficácia, raciocínio verbal e desempenho acadêmico em estudantes. Foram avaliados 57 alunos da rede particular de ensino do sexto e do sétimo ano do ensino fundamental de escolas particulares da cidade do Rio de Janeiro, com faixa etária variando de 10 a 14 anos; 34 do sexo masculino e 23 do sexo feminino. Os instrumentos utilizados foram o Roteiro de Avaliação de Auto-eficácia, a prova de raciocínio verbal da BPR-5 e as notas das avaliações escolares de Portugu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
4
0
4
Order By: Relevance
“…The results show that, according to the literature, school performance is related to different cognitive abilities, intelligence Dodonova & Dodonov, 2012;Lemos et al, 2008;Oliveira & Soares, 2011;Spinath et al, 2010), oral language (Capovilla & Dias, 2008;Dias & Seabra, 2012;Mokhtari & Niederhauser, 2013;Piccolo & Salles, 2013;Skibbe et al, 2008;Tenório & Ávila, 2012), and EF (Blair & Diamond, 2008;Diamond, 2013;Fonseca et al, 2015;Piccolo & Salles, 2013;Seabra et al, 2014). Attention was the only one that did not correlate with children school performance.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The results show that, according to the literature, school performance is related to different cognitive abilities, intelligence Dodonova & Dodonov, 2012;Lemos et al, 2008;Oliveira & Soares, 2011;Spinath et al, 2010), oral language (Capovilla & Dias, 2008;Dias & Seabra, 2012;Mokhtari & Niederhauser, 2013;Piccolo & Salles, 2013;Skibbe et al, 2008;Tenório & Ávila, 2012), and EF (Blair & Diamond, 2008;Diamond, 2013;Fonseca et al, 2015;Piccolo & Salles, 2013;Seabra et al, 2014). Attention was the only one that did not correlate with children school performance.…”
Section: Discussionmentioning
confidence: 64%
“…The first model showed that general intelligence is able to significantly explain the performance of children, which was expected, according to the review of previous studies in this area Lemos et al, 2008;Dodonova & Dodonov, 2012;Oliveira & Soares, 2011;Spinath et al, 2010;Zampieri et al, 2012). It is important to remember that the study sample did not include participants with intellectual disabilities; therefore, the analyses took into account the less extreme variations in this skill.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Alguns estudos fazem referência à autoefi cácia acadêmica (Arens, Craven, Yeung, & Hasselhorn, 2011;Rodrigues & Barreira, 2007;Soares & Oliveira, 2011), mas muitos se atêm a aspectos mais específi cos considerando, por exemplo, autoefi cácia matemática (Chen, 2003;Torisu & Ferreira, 2011).…”
Section: Solução De Problemas E Crenças De Autoefi Cáciaunclassified